Patternmaking as Vehicle for Social Change: A Participatory Practice Research with Diverse Women’s Communities in London - Monteiro, Joana (ZoneModa Journal, 2023)
Often criticised for its negative social impacts, fashion can also be a powerful tool to improve people’s lives. Many companies, research and community projects are creating a counter-narrative to the mainstream fashion system by including the voices and practices of marginalised communities. In community-based research, many fashion and textile techniques are used to engage people and foster social change, but there are limited examples of patternmaking being used in a participatory way for this purpose. Patternmaking is commonly considered a technical and uncreative step in the fashion design process. This research however presents patternmaking as a creative practice of fashion design and explores it through the lens of fashion design for social innovation. The aim is to explore how patternmaking and garment making can foster social change within diverse women’s communities in London. The project employs participatory practice research as research strategy and the approach consists in a series of participatory making workshops, that progressively lead the participants to develop their own creative practice. Two series of workshops with women living in a deprived area of London have shown that participating in the workshops has led to skill acquisition, creativity development, community engagement and the improvement of wellbeing and self-confidence.